THE EFFECT OF ADVERTISING AND BRAND AMBASSADOR ON THE PURCHASE DECISION OF SUNSILK SAMPO (SURVEY ON STUDENTS OF FEB UNPAK MANAGEMENT PROGRAM) - Arie Wibowo Irawan; Oktori Kiswati Zaini; Putri Elisa (Politeknik Negeri Semarang, 2022)
Competition in the shampoo industry in Indonesia is very tight, companies must prepare a good strategy in promoting their products, one of which is by using advertisements and also a brand ambassador. This study aims to analyze the effect of advertising and brand ambassadors on purchasing decisions for Sunsilk shampoo. This study uses quantitative methods with associative research types. With the respondents being students of FEB Unpak management study program. Respondents were selected using a disproportionate stratified random sampling method with a total of 100 respondents based on the calculation of the Slovin formula. Data was collected through questionnaires and the analytical methods used were descriptive analysis, classical assumption test, multiple linear regression, hypothesis testing and coefficient of determination. The results showed that advertising had a significant effect on purchasing decisions for Sunsilk shampoo, while brand ambassadors had no significant effect on purchasing decisions. Based on the F test, advertisements and brand ambassadors simultaneously or jointly have a significant effect on purchasing decisions for Sunsilk shampoo. In addition, advertising and brand ambassadors contributed 48.9% and 51.1% contributed by other variables not examined in this study.